PERSEPSI DOSEN JURUSAN P.IPS FKIP UNIVERSITAS RIAU TERHADAP DEMONSTRASI MAHASISWA (Studi Kasus Demonstrasi karhutla 2019) - Meryo Tiani; Hambali Hambali; Ahmad Eddison (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the perception of lecturers majoring in Social Sciences Education (P.IPS) FKIP Riau University to student demonstration (case study of forest and land fire (Karhutla) demonstrations 2019). Data management is performed using quantitative descriptive analysis. Samples from this study were all lecturers majoring in P-IPS FKIP Riau University as many as 44 lecturers divided into 3 departments namely Economic Education, Parallel Education and Pancasila and Citizenship Education (PPKn) with a population of 44 lecturers. The sample collection technique in this study uses the Nonprobability technique that is saturated sample or often called total sampling. Data collection activities carried out by observation (observation), interviews, questionnaires and documentation. This research is descriptive in nature which aims to describe the conditions or phenomena that exist in the field, then the data obtained will be analyzed with a quantitative descriptive system with a percentage. Based on the results of the study it was found that the results of the calculation of the average value of the alternative answers of dominant respondents is 68.77% where this range is in the